Assessment of energy potential for heat recovery in the EU industry - Panayiotou, Gregoris; Agathokleous, Rafaela; Florides, Georgios A.; Christodoulides, Paul (My University, 2020)
Thermal processes account for 70% of the EU industry final energy, with 30% thereof being wasted through losses. This fact has been a motivating factor toward applying various technologies and methods for waste heat recovery. Already such technologies exist and are applied in many industrial sectors, while some “new” technologies have also been tested or suggested. It is therefore useful to obtain insight information into such processes, together with their temperature ranges and, hence, assess the potential market for each industrial sector. Here such an attempt is made, based on existing literature. Estimates on the total energy that can be recovered through the EU industry are given and a special case study on the important Iron and Steel industry is presented. This kind of information can be useful for the improvement of existing and the development of “new” technologies or techniques.
Keywords: Waste heat recovery; WHR potential estimation; WHR technologies; Iron and steel